Penghargaan Islam terhadap Kesetaraan Gender: Islamic Appreciation of Gender Equality - Al Furqon (An-Nisa’ Journal of Gender Studies, 2012)
Recently, some parties have considered that the interpretation of scholars regarding the verses about women in the Qur'an is too textual, resulting in a narrow and non-universal understanding. Among the verses that are often cited as a form of gender bias is Surah al-Nisa verse 4, which states that men are leaders of women. Meanwhile, feminists consider this verse to be a form of " religiously justified gender injustice," necessitating critical study that produces a different interpretation. This feeling of being treated unfairly and positioned as subordinate has prompted them to conduct interpretive studies that differ from the historical-contextual approach, leading to equal rights and obligations for men and women. This paper seeks to explain Islam's appreciation Islam's respect for gender equality by referring to the primary sources of Islamic teachings, namely the Qur'an and Hadith, to answer the doubts and accusations of feminists against Islamic teachings, which are considered to still be gender biased. Belakangan ini, beberapa pihak menganggap bahwa penafsiran para ulama terhadap ayat-ayat wanita dalam Al-Qur'an terlalu tekstual sehingga menghasilkan pemahaman yang sempit dan tidak universal. Di antara ayat yang sering disebut sebagai bentuk bias terhadap gender adalah surat al-Nisa ayat 4 yang menyebutkan bahwa laki-laki adalah pemimpin bagi perempuan. Sementara kaum feminis menganggap ayat ini sebagai bentuk" ketidakadilan gender yang dijustifikasi agama”, sehingga perlu dilakukan kajian kritis yang menghasilkan penafsiran berbeda. Perasaan diperlakukan kurang adil dan diposisikan sebagai subordinat ini mendorong mereka untuk membuat kajian tafsir yang berbeda dengan pendekatan historis kontekstual yang berujung pada kesetaraan hak dan kewajiban bagi laki-laki dan perempuan.Tulisan ini berusaha menjelaskan penghargaan Islam terhadap kesetaraan gender dengan merujuk pada sumber-sumber primer ajaran Islam yaitu al-Qur'an dan al-Hadits untuk menjawab keraguan dan tuduhan kaum feminis terhadap ajaran Islam yang dianggap masih bias gender.